2015
DOI: 10.3139/217.2789
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Thermal Stability and Flame Retardant Properties of Synthesized Halloysite Nanotubes (HNT)/Ethylene Propylene Diene Monomer (EPDM) Nanocomposites

Abstract: In this work, Halloysite Nanotube (HNT) was synthesized, using a modified method, from kaolin clay. The scanning electron microscopy (SEM) of the synthesized HNT revealed that many of the nanotubes were tubular; however, spherical and semi-spherical, platy and semi rolled structures were also observed. Fire retardant EPDM compounds composed of typical flame retardants (FR), deca-bromo diphenyl oxide (DBDPO), antimony oxide (Sb 2 O 3 ), talc and carbon black were prepared. Three elastomer compounds, with 5, 10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Moreover, the variation of ∆a indicates the composites become much greener. In addition, the trend of changed ∆b of composites show that the composites become more bluer [9] [10] [17][18][19][20][21].…”
Section: Colorimetry Measurement Of Epdm/sio 2 /Cnt Compositesmentioning
confidence: 99%
“…Moreover, the variation of ∆a indicates the composites become much greener. In addition, the trend of changed ∆b of composites show that the composites become more bluer [9] [10] [17][18][19][20][21].…”
Section: Colorimetry Measurement Of Epdm/sio 2 /Cnt Compositesmentioning
confidence: 99%
“…52 Therefore, the samples are expected to show higher crystallinity and T m as compared to the previous samples. Based on the mechanical properties, a high content of lignin and silica together activates the paste effect and for the lower amounts, lignin may act as a plasticizer, as a result, for lower filler content, both T m and H c show a sensible drop in their values compared with the PSRS0 and RS or HWRS-filled samples, although by increasing the filler content silica would actively act as a nucleating agent 53 and somehow reciprocate the lignin plastication effect. The effect of silica is obvious in X t , as the value is increased from 10.91 to 14.32%.…”
Section: Thermal Analysismentioning
confidence: 99%
“…HNTs with molecular formula (Al 2 Si 2 O 5 (OH) 4 •nH 2 O) are similar to kaolin, but their hollow structure gives reason to hope that it can be considered as a flame retardant additive [39,41]. Previous studies have uncovered the fact that addition of HNTs at high loading levels (more than 20 wt.%) and/or in combination with conventional flame retardants to polypropylene [42], poly (vinyl alcohol) [43], polyamide 6 [44,45], low-density polyethylene [38,46], ethylene propylene diene monomer [47], and epoxy resin [48,49] could to a large extent improve flame retardancy of polymers. Moreover, recent studies have shown that incorporation of HNTs has a positive effect on thermal degradation of epoxy-based intumescent fire retardant coatings [50].…”
Section: Introductionmentioning
confidence: 99%